The Analysis of Excellent Economic Sector in Regional Economic Building in Kediri City 2012–2015 - Sari, T P; Rahmawati, F (KnE Social Sciences, 2018)
The purpose of this study was to determine (1) the economic sectors that excel in any category of contribution and growth; (2) the sector that can create jobs to the maximum; (3) The most efficient sectors to be developed; and (4) the growth pattern of economic sectors in the area of Kediri. This type of research is quantitative descriptive. with the calculation of secondary data for the period 2012-2015. The analytical method used is the analysis of Location Quotient (LQ), Growth Ratio Model (GRM), Elasticity Employment, ICOR and Typology Klassen. The results showed that (1) the manufacturing industry is the only comparative advantage of Kediri based on criteria of contribution, while the dominant sector is based on growth the is trade, hotels and restaurants; transport and communications; and the services sector; (2) sectors with potential to absorb labor maximum is agriculture, livestock, forestry and fisheries; the construction sector; trade, hotels and restaurants; and transport and communications; (3) an efficient sector to be developed in the town of Kediri, namely agriculture, livestock, forestry and fisheries; transport and communications; the financial sector, real estate and business services; and the services sector; (4) based on (3) an efficient sector to be developed in the town of Kediri, namely agriculture, livestock, forestry and fisheries; transport and communications; the financial sector, real estate and business services; and the services sector; (4) based on the growth pattern of each sector there is no sector that is advancing and growing rapidly or quadrant I, the sector that includes quadrant II is a sector forward but stressed that is manufacturing sector, quadrant III potential sectors there are mining and quarrying, trade, hotels and restaurants, and the services sector, while the five other sectors is relatively lagging sector. Keywords: Leading Economic Potential, Economic Development